A bio-economic model for cost analysis of alternative management strategies in beef finishing systems. (April 2020) - Kamilaris, C.; Dewhurst, R.J.; Vosough Ahmadi, B.; Crosson, P.; Alexander, P.
Highlights: Only thirteen of forty beef production systems in Scotland found to be profitable. Short duration steer systems showed higher financial returns for continental breeds. Selecting for feed efficiency or including subsidies turned many systems profitable. The financial impact of selection for feed efficiency is greater in steer systems. Abstract: Global population growth together with rising incomes is increasing the demand for meat-based products. This increases the need to optimize livestock production structures, whilst ensuring viable returns for the farmers. On a global scale, beef producers need tools to assist them to produce more high-quality products whilst maintaining economic efficiency. The Grange Scottish Beef Model (GSBM) was customized to simulate beef finishing enterprises using data from Scottish beef finishing studies, as well as agricultural input and output price datasets. Here we describe the model and its use to determine the cost-effectiveness of alternative current management practices (e.g. forage- and cereal-based finishing) and slaughter ages (i.e. short, medium or long finishing duration). To better understand drivers of profitability in beef finishing systems, several scenarios comparing finishing duration, gender, genetic selection of stock for growth rate or feed efficiency, as well as financial support were tested. There are opportunities for profitable and sustainable beef production in Scotland, for both cereal and forage based systems, particularly when aiming for a younger age profile at slaughtering. By careful choice of finishing systems matched to animal potential, as well as future selection of high performing and feed efficient cattle, beef finishers will be able to enhance performance and increase financial returns.